Exploring Interactive Sound Design for Auditory Websites - Zhang, Lotus; Shao, Jingyao; Liu, Augustina Ao; Jiang, Lucy; Stangl, Abigale; Fourney, Adam; Morris, Meredith Ringel; Findlater, Leah (CHI 2022, 2022)
Auditory interfaces increasingly support access to website content, through recent advances in voice interaction. Typically, however, these interfaces provide only limited audio styling, collapsing rich visual design into a static audio output style with a single synthesized voice. To explore the potential for more aesthetic and intuitive sound design for websites, we prompted 14 professional sound designers to create auditory website mockups and interviewed them about their designs and rationale. Our findings reveal their prioritized design considerations (aesthetics and emotion, user engagement, audio clarity, information dynamics, and interactivity), specific sound design ideas to support each consideration (e.g., replacing spoken labels with short, memorable audio expressions), and challenges with applying sound design practices to auditory websites. These findings provide promising direction for how to support designers in creating richer auditory website experiences.